De novo design of Au36(SR)24 nanoclusters - Xu Liu (Nature Portfolio, 2020)
The discovery of atomically precise metal nanoclusters is generally unpredictable, and there are few examples of their rational synthesis. Here, the authors report the de novo design of Au36(SR)24 nanoclusters, from theoretical prediction to experimental synthesis and characterization of physicochemical properties.